2003
DOI: 10.1055/s-2003-43254
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proton Magnetic Resonance Spectroscopy of Children with Adrenoleukodystrophy Before and After Hematopoietic Stem Cell Transplantation

Abstract: About 35-40 % of boys with X-linked adrenoleukodystrophy (ALD) develop a rapidly progressive cerebral form which leads to severe neurologic disability and death within 3-5 years after onset of clinical symptoms. Because previous proton magnetic resonance spectroscopy (MRS) studies of ALD identified metabolite patterns characteristic of demyelination, gliosis, and neuroaxonal loss, this work tested the hypothesis that MRS--apart from indicating disease progression--provides criteria for the outcome after hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…ccALD, the most rapidly progressing phenotype, occurs in boys ages 2–12 and is characterized by sudden inflammatory demyelination in the brain and death within a few years [ 13 , 14 ]. ccALD affects about 40% of males with an ABCD1 mutation [ 15 , 16 ]. MRI observation of gadolinium enhancement in the brain remains the only method to detect this progression [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…ccALD, the most rapidly progressing phenotype, occurs in boys ages 2–12 and is characterized by sudden inflammatory demyelination in the brain and death within a few years [ 13 , 14 ]. ccALD affects about 40% of males with an ABCD1 mutation [ 15 , 16 ]. MRI observation of gadolinium enhancement in the brain remains the only method to detect this progression [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The review identified 26 studies on either the natural history or outcome following transplantation [ 6 , 9 11 , 35 , 40 62 ]. For patients with CCALD, there is no direct comparative evidence on survival with and without HSCT.…”
Section: Methodsmentioning
confidence: 99%
“…For patients with CCALD, there is no direct comparative evidence on survival with and without HSCT. Survival and time to progression without transplantation were estimated from the Mahmood et al study [ 11 ], selected from the 26 studies [ 6 , 9 11 , 35 , 40 62 ] as it presented data on a large cohort, 283 patients, with follow-up of up to 30 years. The model assumed that CCALD patients start off with mild to moderate disease before progressing to severe CCALD indicated by developing two or more neurological deficits with a mean time to progression of 1.6 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale of the HCT relies on the hypothesis that fully functional, donated bone marrow cells can cross the blood brain barrier of the recipient and exert beneficial effects on the mechanisms leading to CNS demyelination. The first report about a favorable effect of HCT in a CCALD patient was published in 1990 [95] and several subsequent reports in small patients series showed positive results [96][97][98][99][100]. Follow-up studies demonstrated that the beneficial effect is maintained for 5-10 years [101,102].…”
mentioning
confidence: 99%